Primary rectal tuberculosis mimicking malignancy - Jagtap, Sunil V.; Ingale, Shivani H.; Jagtap, Swati S. (International Surgery Journal, 2017)
Primary rectal involvement by tuberculosis infection is rare. We present a relatively uncommon case of primary rectal tuberculosis. A 35-year-old male patient presented with history of long duration of anorexia, altered bowel habits, painful defecation, fever, and rectal bleeding. On clinical and radiological finding case was suspected of rectal malignancy. The proctoscopic biopsy was performed. On histopathology, it was diagnosed as rectal tuberculosis. We are presenting this case for its rarity, mimicking malignancy and difficulty in diagnosis.